Respuesta :

Answer:

Hopes this SS Helps you

Step-by-step explanation:

XOXO

KIT

Ver imagen Аноним

Answer:

x = 2, x = 4

Step-by-step explanation:

Begin by letting f(x) = 0 , that is

x² - 6x + 8 = 0

Consider the factors of the constant term (+ 8) which sum to give the coefficient of the x- term (- 6)

The factors are - 2 and - 4 , since

- 2 × - 4 = + 8 and - 2 - 4 = - 6 , then

(x - 2)(x - 4) = 0

Equate each factor to zero and solve for x

x - 2 = 0 ⇒ x = 2

x - 4 = 0 ⇒ x = 4

ACCESS MORE